Perbandingan Pemeriksaan Trombosit Cara Rees Ecker dan Amonium Oxalate dengan Gold Standard Hematology Analyzer - Raga, Erly; Gustiarni R, Dhiana (Cerdika: Jurnal Ilmiah Indonesia, 2022)
In some clinical laboratories, especially in laboratories at health center and in small clinics outside big cities, the manual method of counting platelets is still widely used, in medium to major laboratories, manual methods have been abandoned and have changed to automatic methods, this is due to patients in the laboratory. Medium-sized hospitals tend to be more than health center laboratories so that health center laboratory workers prefer to use the manual platelet count method. The purpose of this study was to find out how far the results of the rees ecker and amonium oxalate examination of platelets differ from the gold standard hematology analyzer, which of the two methods is closest to the hematology analyzer. So that it can be a reference for health workers and the health center themselves to choose which manual examination method is better, i.e. the results are closer to the results of the gold standard hematology analyzer. The type of research conducted is comparative research, which is comparing the differences in the value or data of one variable with another. Based on the results of manual platelet examination using amonium oxalate, the results are closer to the results of automatic platelet examination, namely the gold standard hematology analyzer, thus manual platelet examination with amonium oxalate can be an option for smallclinics.